PSTPIP2, a Protein Associated with Autoinflammatory Disease, Interacts with Inhibitory Enzymes SHIP1 and Csk - Drobek, Aleš; Kralova, Jarmila; Skopcova, Tereza; Kucova, Marketa; Novák, Petr; Angelisová, Pavla; Otahal, Pavel; Alberich-Jorda, Meritxell; Brdicka, Tomas (The Journal of immunology, 2015)
Mutations in the adaptor protein PSTPIP2 are the cause of the autoinflammatory disease chronic multifocal osteomyelitis in mice. This disease closely resembles the human disorder chronic recurrent multifocal osteomyelitis, characterized by sterile inflammation of the bones and often associated with inflammation in other organs, such as the skin. The most critical process in the disease's development is the enhanced production of IL-1β. This excessive IL-1β is likely produced by neutrophils. In addition, the increased activity of macrophages, osteoclasts, and megakaryocytes has also been described. However, the molecular mechanism of how PSTPIP2 deficiency results in this phenotype is poorly understood. Part of the PSTPIP2 inhibitory function is mediated by protein tyrosine phosphatases from the proline-, glutamic acid-, serine- and threonine-rich (PEST) family, which are known to interact with the central part of this protein, but other regions of PSTPIP2 not required for PEST-family phosphatase binding were also shown to be indispensable for PSTPIP2 function. In this article, we show that PSTPIP2 binds the inhibitory enzymes Csk and SHIP1. The interaction with SHIP1 is of particular importance because it binds to the critical tyrosine residues at the C terminus of PSTPIP2, which is known to be crucial for its PEST-phosphatase-independent inhibitory effects in different cellular systems. We demonstrate that in neutrophils this region is important for the PSTPIP2-mediated suppression of IL-1β processing and that SHIP1 inhibition results in the enhancement of this processing. We also describe deregulated neutrophil response to multiple activators, including silica, Ab aggregates, and LPS, which is suggestive of a rather generalized hypersensitivity of these cells to various external stimulants.
Keywords: Animals; zánět; buněčné linie; vazebná místa; Adaptor Proteins, Signal Transducing; Osteomyelitis; makrofágy; sekvence aminokyselin; adaptorové proteiny signální transdukční; megakaryocyty; fosfatasy; vazba proteinů; Osteoclasts; cytoskeletální proteiny; Molecular Sequence Data; osteomyelitida; Macrophages; Mice; signální transdukce; Amino Acid Sequence; Mice, Inbred BALB C; myši; osteoklasty; Signal Transduction; Cell Line; Inflammation; molekulární sekvence - údaje; Cytoskeletal Proteins; Interleukin-1beta; fosforylace; myši inbrední BALB C; skupina kinas odvozených od src-genu; Neutrophils; neutrofily; src-Family Kinases; interleukin-1beta; zvířata; Phosphoric Monoester Hydrolases; Megakaryocytes; Protein-Tyrosine Kinases; Protein Binding; Phosphorylation; tyrosinkinasy; Binding Sites